The Influence Of Environmental Costing, Sustainable Per-formance Measurement, and Decision Making on Sustaina-bility Management Accounting - Beby Wahyu Andre; Sari Indah Setio Maria Savsavubun; Gabriella Afe Glorya; Febri Risnandia Wibowo Putri; Maria Yovita R.Pandin (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of Environmental Costing, Sustainable Performance Measurement, and Decision Making on Sustainability Management Accounting (SMA) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. The research method uses a quantitative approach with a descriptive and explanatory design. The sample was determined through a purposive sampling method with the criteria of companies that consistently publish annual reports, sustainability reports, and participate in the PROPER program. The data analysis technique used multiple linear regression with classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation. The results of the study indicate that simultaneously Environmental Costing, Sustainable Performance Measurement, and Decision Making have a negative and insignificant effect on Sustainability Management Accounting. Partially, the three independent variables also did not show a significant effect on SMA. This finding indicates that these sustainability elements have not been effectively integrated into the company's management accounting system. This study shows the need to increase management commitment and develop a more structured sustainability information system in order to support strategic decision making in line with sustainability principles.